2003
DOI: 10.1002/anie.200351640
|View full text |Cite
|
Sign up to set email alerts
|

Glycotentacles: Synthesis of Cyclic Glycopeptides, Toward a Tailored Blocker of Influenza Virus Hemagglutinin

Abstract: Influenza virus infection is initiated by the binding of hemagglutinin (HA), a viral carbohydrate-binding membrane protein, to sialic acid-containing oligosaccharides, such as GM3 trisaccharide [Neu5Aca(2,3)Galb(1,4)Glc], on the host cell surfaces.[1] Since this molecular-recognition process leads to the host cell-virus adhesion stage, molecules with a high affinity for the viral HA would be potent candidates for blockers of the influenza virus. Various types of HA blockers carrying sialooligosaccharides have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…They observed that the tridentate sialyl lactose ligand on a particular cyclic peptide template, where all the three ligands were directed outward from the cyclic peptide ring, exhibited highest affinity (K d = 0.65 mM) for HA protein on the SPR sensor surface (see Figure 4e). 98 Here, the distance between binding sites on the hemagglutinin structures needed to be known in advance in order to simultaneously bridge and reinforce the bond formation between the tripod units and binding pockets at the HA head. Using longer PEG segments not only raised the probability of the ligand and receptor binding, but also greatly increased the entropic cost through molecular conformations of the tethered chains.…”
Section: Ligand Densitymentioning
confidence: 99%
“…They observed that the tridentate sialyl lactose ligand on a particular cyclic peptide template, where all the three ligands were directed outward from the cyclic peptide ring, exhibited highest affinity (K d = 0.65 mM) for HA protein on the SPR sensor surface (see Figure 4e). 98 Here, the distance between binding sites on the hemagglutinin structures needed to be known in advance in order to simultaneously bridge and reinforce the bond formation between the tripod units and binding pockets at the HA head. Using longer PEG segments not only raised the probability of the ligand and receptor binding, but also greatly increased the entropic cost through molecular conformations of the tethered chains.…”
Section: Ligand Densitymentioning
confidence: 99%
“…The shape of the glycopeptide protein scaforld, which is determined by the amino acid sequences employed, is also found to be significant in determining the inhibitory activity. 87) We also developed glycopolymers containing multivalent sialyloligosaccharides (Neu5Aca2-3Galb1-4GlcNAcb1-, Neu5Aca2-6Galb1-4GlcNAcb1-, Neu5Aca2-3Galb1-3Gal-NAca1-, Neu5Aca2-3Galb1-3GalNAcb1-) with a poly (Lglutamic acid) backbone, 88) triantennary oligosaccharide branches (Neu5Aca2-3Galb1-4GlcNAcb1-, Neu5Aca2-6Galb1-4GlcNAcb1-) with a polyacrylamide backbone, 89) and sialyllactose (Neu5Aca2-3Galb1-4Glcb1-; Neu5Aca2-6Galb1-4Glcb1-) with a polystyrene backbone 90) that inhibit the receptor binding function of the hemagglutinin of influenza viruses. The glycopolymer inhibited the hemagglutination of influenza A virus, and its activity level was 10 3 -times higher than that of the oligosaccharide itself, indicating that clustering of the sugar chain in the polymer backbone may be important for inhibitory activity of the viral hemagglutinin.…”
Section: Development Of New Anti-influenza Drugs -A New Influenza Virmentioning
confidence: 99%
“…A cyclic peptide presenting three 3-sialyllactoside units ( 1 0 ) was prepared by chemoenzymatic method using transglutaminase and glycosyltransferase [52] by S.-I. Nishimura's group.…”
Section: 7mentioning
confidence: 99%